Penguatan Keaktifan Belajar Siswa melalui Penerapan Model Problem Based Learning dalam Kegiatan Pengabdian Pendidikan di SMA Negeri 6 Palembang - Nawfal Fadhlullah Arkan; Santi Noor Rahmah; Rose Helena; Fernanda; Ariel Kurnia Putra; M. Ridho Prasetyo; Harry Christian; M. Idris (PT. Hasba Edukasi Mandiri, 2026)
This article describes the strengthening of students' active learning through the implementation of Problem Based Learning (PBL) during the educational service and School Field Introduction Program (PLP) at SMA Negeri 6 Palembang. The study used a descriptive qualitative approach based on classroom observation, photo documentation, and field notes. The focus was not to measure learning outcomes statistically, but to portray how PBL was planned and implemented in a real school context. PBL was applied by placing contextual problems at the beginning of learning, guiding students to discuss in groups, encouraging them to ask questions, present ideas, respond to peers, and complete learning tasks. The findings show that students' active learning appeared in several forms: paying attention to explanations and media, participating in group discussion, sharing opinions, presenting group work, and completing assignments after discussion. PLP students played an important role as learning facilitators who provided prompts, accompanied small groups, and helped teachers maintain classroom interaction. Several obstacles were found, such as uneven student confidence, limited time, repeated guidance needs, and the importance of clear media. These challenges were addressed through concise instructions, small-group assistance, simple learning media, and closing reflection.